Duhovi Rastlin, Duša Stare Vere: The Use of Plants in Sacred Rituals Among Nature Worshippers in Slovenia - Fatur, Karsten (The pomegranate, 2020)
Native Faith and nature-worshiper groups in Slovenia frequently utilize "sacred" plants in their rituals. Most participants identified with the terms Rodnovera/Starovera in regards to naming their beliefs, or preferred to eschew labels. A variety of plants were used for both sacred and secular purposes, with eighty-four categories emerging when participants' lists were combined. The most frequently mentioned were Cannabis spp., Hypericum perforatum, and Salvia spp., with the latter two also being the most commonly co-occurring plants on lists. The interviews and plants used display the integral role that plants play in the sacred ritual life of nature worship groups in Slovenia, and underline the importance of the symbolic nature of the plants, or the plant's "spirit." These characteristics were of greater importance than physical properties, showing the importance of symbolic relations in how the Pagan nature worshipers of Slovenia connect with their divine conceptions of nature.